A numerical hydro-geotechnical model for marine gravity structures. (October 2016) - Elsafti, H.; Oumeraci, H.
Abstract: A new finite-volume solver named " geotechFoam " is developed within OpenFOAM® 1 for modelling soil-structure-interaction for marine gravity structures. The fully-coupled and fully-dynamic Biot's governing equations are solved in a segregated approach. Two simplifications of the governing equations are introduced and tested. The spatial domain is composed of several zones with different material properties and/or constitutive models. A multi-yield surface plasticity model is implemented to simulate soil response under cyclic loads. Moreover, soil-structure interaction is modelled via a frictional contact model and boundary conditions accounting for skeleton-pore fluid coupling. Five benchmark cases and two sets of physical model tests are applied for the validation.